Analysis of performance development in wrestling during the Olympic cycle 1992 - 1996 and conclusion - Tünnemann, H. (1996)
Preface 1 General developmental tendencies 2 Performance development in the Olympic cycle 1992/96 2.1 Country specific developments 2.2 Age structure of successful wrestlers 2.3 State of development of selected performance features 2.3.1 Strategic and tactical aspects of combat behaviour 2.3.2 State of development of technico-tactical performance features 2.3.2.1 Greco-Roman wrestling 2.3.2.2 Freestyle wrestling 2.3.3 Individualisation of combat behaviour 3 Conclusions for future developments